Importance of Temporal Analyzes for the Exploration of the Posturographic Correlates of Emotional Processing - Mouras, Harold; Lelard, Thierry (Frontiers in Behavioral Neuroscience, 2018)
Over the last two decades, affective and social neurosciences converged on the study of motor correlates of emotional and motivational information processing. Posturography appeared as a good experimental method to address this question. The use of this method to explore emotional and motivation processing remains recent. Here, we summarize several important arguments showing the importance to explore the temporal aspects of these responses regarding the complexity of the link between emotional information’s parameters (such as arousal) and the corresponding neural processes.